2015
DOI: 10.4236/jct.2015.611105
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of Clinicoepidemiological Aspects of Nasopharyngeal Cancer at NCI-Cairo (2000-2010)

Abstract: Aim of Work: The aim of this work was to study the clinico-epidemiological characteristics of the patients with nasopharyngeal carcinoma (NPC), analyse the prognostic factors of the disease and to analyse the results of different treatment modalities and their effect on loco-regional, distal metastatic disease control and both overall survival (OS) and disease free survival (DFS) rates. Patients and Methods: This is a retrospective study reviewing all adult nasopharyngeal carcinoma (NPC) patients who presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…WHO type III was the common HPE variant observed by Ibrahim et al [43], Sharma et al [34] similar results were seen in our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…WHO type III was the common HPE variant observed by Ibrahim et al [43], Sharma et al [34] similar results were seen in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly in our study, majority of patients presented with stage III and IV 68.2 %. Amaro et al [39] showed 54 % patient in Stage IV, Downing et al [40] showed 92 % presented in stage III, Tiong et al [41] showed 85 % of the patient presented in advanced stage (stage III and IV), Skinner et al [42] showed 70 % of patients presented in Stage III disease and Ibrahim et al [43] also showed the advanced stage 86 % presentation of the patients in stage III and IV.…”
Section: Discussionmentioning
confidence: 99%